2009
DOI: 10.1007/s11856-009-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

Poisson approximation for non-backtracking random walks

Abstract: Random walks on expander graphs were thoroughly studied, with the important motivation that, under some natural conditions, these walks mix quickly and provide an efficient method of sampling the vertices of a graph. The authors of [2] studied non-backtracking random walks on regular graphs, and showed that their mixing rate may be up to twice as fast as that of the simple random walk. As an application, they showed that the maximal number of visits to a vertex, made by a non-backtracking random walk of length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…A nonbacktracking random walk (NBRW) W of length l > 0 starting from a node is a random walk in l steps so that in each step the walker picks a neighbor uniformly at random and moves to that neighbor with an additional property that the walker never traverses an edge twice in a row. Further information about NBRWs can be found in [1] and [2]. Here we consider two families of -regular graphs, namely high-degree graphs, where = (log n) and low-degree graphs where, = O(log n).…”
Section: Our Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nonbacktracking random walk (NBRW) W of length l > 0 starting from a node is a random walk in l steps so that in each step the walker picks a neighbor uniformly at random and moves to that neighbor with an additional property that the walker never traverses an edge twice in a row. Further information about NBRWs can be found in [1] and [2]. Here we consider two families of -regular graphs, namely high-degree graphs, where = (log n) and low-degree graphs where, = O(log n).…”
Section: Our Resultsmentioning
confidence: 99%
“…It seems that the previous works could only handle any three of the four properties. In a different context, Alon and Lubetzky [2] showed that if a particle starts a NBRW of length n on an n-vertex regular expander graph with high-girth then the number of visits to nodes has a Poisson distribution. In particular, they showed that the maximum number of visits to a node is at most (1+o(1))⋅ log n log log n .…”
Section: Comparison With Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Since the non-backtracking condition puts no restriction on the first step, it is clear thatà (1) = A. Forà (2) , note that A 2 counts all walks of length 2, so we must simply subtract off those that backtrack. The only walks of length 2 that backtrack are those that move from a vetex to a neghbor, then return immediately.…”
Section: Non-backtracking Random Walksmentioning
confidence: 99%
“…The convergence and mixing rate of non-backtracking random walks is studied in [1,4,8] and [9]. The distribution of the number of visits of a random walk to a vertex is studied in [2], and [3] studies non-backtracking random walks on the universal cover of a graph. In [10], non-backtracking random walks are used to study spectral clustering algorithms.…”
Section: Introductionmentioning
confidence: 99%